A CASE REPORT OF IMMUNOSUPRESSION RELATED COMPLICATIONS IN A KIDNEY TRANSPLANTED PATIENT - Spasovska Vasilova, Adrijana; Trajkova, Sanja; Simonovska, Elena; Stojanoska Godjoska, Simona; Stojanoska, Ana; Nikolov, Igor; Rambabova Bushljetik, Irena; Trajcheska, Lada; Spasovski, Goce (Journal of Morphological Sciences, 2020)
Immunosuppressed transplant recipients have a higher rate of prolonged survival with a functioning graft, but also prolonged exposure to complications of chronic immunosuppression. Registry data found cancer to be the third most common cause of death after cardiovascular accidents and infections in these patients. In the following case, we present a kidney transplanted patient, successfully treated for Diffuse large B-cell lymphoma , generalized Herpes Zoster , and CMV infection . The patient was a 60 years-old man with a kidney transplant from a cadaver 5 years ago. After the transplantation, no complications occurred. He regularly referred for medical monitoring, and was adherent to medical treatment and investigations. His long term immunosuppressive therapy consisted of a low dose of corticosteroids, tacrolimus, and mycophenolic acid. The patient presented with acute pain and tenderness all over the abdomen that lasted for a few hours. After CT imagining confirmed intussusception at left colic flexure, urgent surgery was performed. Tissue sampling diagnosed Large B-cell lymphoma. The patient underwent 4 cycles of dose-rationalized R-CHOP therapy with a normal PET scan afterward. Herpes Zoster generalized infection and CMV occurred in two months. Treatment with acyclovir was successful. The regular immunosuppressive regime was re-introduced, consisting only of corticosteroids and sirolimus. The creatinine level remained stable for the next two years, and all subsequent PET scans and CT images were in normal range. The patient remained free of infections as well. Key words :  kidney, transplant, immunosuppression, B-cell lymphoma, malignicy.